Revealing the novel effect of Jinghua Weikang capsule against the antibiotic resistance of Helicobacter pylori - Jia, Xiaofen; Huang, Qiuyue; Lin, Miaomiao; Chu, Yingming; Shi, Zongming; Zhang, Xuezhi; Ye, Hui (Frontiers in Microbiology, 2022)
Background Helicobacter pylori (H. pylori) infects half of the human population globally. Eradication rates with triple or quadruple therapy have decreased owing to the increasing rate of antibiotic resistance. Jinghua Weikang capsule (JWC) is the first and most popular Chinese patent medicine approved by the state for the treatment of gastritis and peptic ulcers caused by H. pylori infection in China. Previous studies have found that JWC has a certain bactericidal effect on drug-resistant H. pylori and its major component, Chenopodium ambrosioides L. inhibits biofilm formation, but the mechanism remains unclear. This study focused on drug-resistant H. pylori and explored whether JWC could reverse drug resistance and its related mechanisms. Method The agar plate dilution method, E-test method, and killing kinetics assay were used to evaluate the bactericidal effect of JWC on antibiotic-resistant H. pylori and its effect on antibiotic resistance. Sanger sequencing was used to detect mutations in drug resistance genes. The crystal violet method, scanning electron microscopy, and confocal laser scanning microscopy were used to evaluate the effects of JWC on biofilms. qPCR was performed to evaluate the effect of JWC on the expression of efflux pump-related genes. qPCR and immunofluorescence were used to evaluate the effects of JWC on H. pylori adhesion. Results JWC showed considerable antibacterial activity against drug-resistant H. pylori strains, with minimum inhibitory concentration (MIC) values ranging from 64 to 1,024 μg/ml. The MIC of metronidazole (MTZ) against H. pylori 26,695–16R decreased from 64 to 6 μg/ml after treatment with 1/2 MIC of JWC. The resistance of H. pylori 26,695–16R to MTZ was reversed by JWC, and its effect was better than that of PaβN and CCCP. H. pylori 26,695–16R is a moderate biofilm-forming strain, and JWC (16–64 μg/ml) can inhibit the formation of biofilms in H. pylori 26,695–16R. JWC reduced the expression of HP0605-HP0607 (hefABC), HP0971-HP0969 (hefDEF), HP1327-HP1329 (hefGHI), and HP1489-HP1487. JWC reduced the adhesion of H. pylori to GES-1 cells and the expression of adhesives NapA, SabA, and BabA. Conclusion The reversal of MTZ resistance by JWC may be achieved through the adhesin/efflux pump-biofilm pathway.